Avaliação da sustentabilidade ambiental do cultivo do peixe Bijupirá (Rachycentron canadum) e sua relação com a macrofauna bentônica de substrato inconsolidado - Campos, Ana Carolina Lustosa Gomes de (2021)
Sediment and benthic macrofauna samples of unconsolidated substrate were analyzed in the cobia fish farming area and in two adjacent areas in the months of April, September and December 2019 and August and November 2020 in the Bananal Cove - Ilha Grande Bay. The circulation of currents along the water column was obtained through an acoustic current profiler by the Doppler effect. Two 24-day anchorages were carried (april and july 2019), recording syzygy and quadrature tidal cycles in both. The results indicated predominance of organisms of the class of gastropods and bivalves in all sampling stations. The species richness and diversity were analyzed together with the organic matter present in the sediments and did not show any correlation. The heterogeneity of the collection points was well marked both for the analysis of sediments and for the biological data, pointing out that several factors can influence the structure of the benthic community. The results indicated, even punctually, that the size of the sediment grains and the distribution of the organisms were not altered by the contribution of organic matter produced in the cobia tanks. The results related to the intensity of the currents in the area, tested the characteristic of low energy in the seabed of in the region Bananal cove, being these insufficient for the dispersion of organic matter to the control areas.